Dynamic response of agricultural production to financial stress using ARDL and QARDL models - Shairil Izwan Taasim; Neilson Teruki; Nur Azmina Binti Tajuddin; Wong Sing Yun (The Publisher, 2025)
The agricultural sector plays a vital role in ensuring food security for Malaysia and is one of the sources of income for the country, growing fast over decade. The Malaysian government has implemented various measures to address the challenges facing the agricultural sector and improve food security in the country. The government has also implemented various initiative such as subsidy for agricultural and government intervention in the market. This study investigates the performance of Malaysia financial stability by examining the short and long run effects on agricultural production. The monthly data selected agricultural products for the period of January 2015 to December 2022 are used for this study. We estimate an ARDL and Quantile ARDL model to analyze the relationship. Our results indicate crude palm oil and natural rubber have an integration with the financial stress. The crude oil palm and rubber have the largest contributions for Malaysia agricultural. Findings suggest addressing the challenges facing the agricultural sector include the stability of financial stress towards improving food security.